INFLUENCE OF TARGET POSITION ON EYE MOVEMENT IN NAVIGATIONAL AND INFORMATIVE TASKS: REINTERPRETATION OF DATA - José Vasconcelos-Raposo (PsychTech & Health Journal)
The main objective of this study is to understand how the target’s position influences eye movement in navigational and informative tasks. The study included 20 university students, 13 females and 7 males, aged between 18 and 44. Participants answered a socio-demographic questionnaire and performed two tasks: navigational and informative. Linear combinations of dependent variables were performed through the MANOVA (2x2) test, which maximized the differences between several conditions of the independent variables. The results indicate that the target’s position in the navigational task significantly influences the eye movement of university students. Additionally, the individual’s position influences eye movement in both navigational and informative tasks. It is concluded that both the target’s position and the individual’s position determine eye movement factors during navigational and informative tasks, highlighting the importance of considering these variables in studies of visual perception and human-computer interaction.